1995
DOI: 10.1093/tropej/41.supplement_1.30
|View full text |Cite
|
Sign up to set email alerts
|

Coverage and Quality of Natal and Postnatal Care: Women's Perceptions, Saudi Arabia

Abstract: This paper discusses natal and postnatal care services in Saudi Arabia, as revealed by the National Maternal & Child Health Survey of 1991. The latter was based on a national random sample of 150 clusters, with 6306 households, from urban and rural areas, of five geographic regions. The target of 6294 ever-married Saudi women, 15-49 years old included 6020 currently married women, of whom 1050 reported a pregnancy. Data on maternal care were analysed, including where and why natal care was attended, and for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Education and employment are thought to empower women to overcome barriers to use, either via better information or improved income. These determinants are seen with postpartum use, and services such as prenatal care in settings as diverse as Saudi Arabia, 1 Karachi, Pakistan, 17 Tunisia and Morocco, 13 Turkey, 18 and a review of studies in the UK 19 . Other factors not measured in our study have been shown to determine the use of postpartum services, namely, maternal age at marriage 20 and use of prenatal care services 21 …”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Education and employment are thought to empower women to overcome barriers to use, either via better information or improved income. These determinants are seen with postpartum use, and services such as prenatal care in settings as diverse as Saudi Arabia, 1 Karachi, Pakistan, 17 Tunisia and Morocco, 13 Turkey, 18 and a review of studies in the UK 19 . Other factors not measured in our study have been shown to determine the use of postpartum services, namely, maternal age at marriage 20 and use of prenatal care services 21 …”
Section: Discussionmentioning
confidence: 66%
“…The traditional six‐week postpartum visit is intended to evaluate women's physical and psychological wellbeing and to address their family planning needs. Uptake of this visit by women in different developing countries varies from high levels (88% in Saudi Arabia 1 ), to very low (6% in Yemen 2 ). The use of health services is known to depend on the physical, economic, and social accessibility of the offered services, as well as on the perceived benefit compared with other opportunity costs.…”
Section: Introductionmentioning
confidence: 99%
“…This also may explain why midwives are preferred as providers of antenatal and delivery care. According to Baldo [15] in rural areas in Saudi Arabia women have a stronger preference for female traditional birth attendants. However, receiving care from a male doctor is possible as long as the social rule of having a female nurse in the consultation room is followed.…”
Section: Resultsmentioning
confidence: 99%
“…Home deliveries are still prevalent in many parts of the world [26]. Women that deliver at home are at high risk of not receiving timely postnatal care [2,[27][28][29][30][31]. They may even be discouraged from seeking postnatal care due to negative attitudes of healthcare providers towards them [32].…”
Section: Barriers To Access Of Postpartum Carementioning
confidence: 99%